Uma experiência de horta escolar como proposta maker para o Ensino de Ciências - Costa, Joanete de Souza (2024)
The Maker teaching proposal is an activity defined as technical knowledge in a marketing way, which allows knowledge and values to be added to the construction in a reflective way and capable of promoting decision-making and also thinking about the objective of their learning, providing autonomy in the construction of prototypes and scientific knowledge. The Activity Theory is the relationship between man and his environment and his psychic functions that act in the search for knowledge, that is, a human activity driven by an objective, thus the activity theory supports us and contributes to the teaching of science, based on a maker proposal for teaching through the STEAM approach in an interdisciplinary approach with the prototyping of a school garden. The STEAM (Science, Technology, Engineering, Arts and Mathematics) approach is a strategy for developing investigative skills in the areas of science or technology, based on the implementation of proposals whose methodology corresponds to Project-Based Learning (PBL). This study aims to investigate how the Maker teaching proposal using a school garden as a socio/cultural context can make science classes more dynamic, promoting more active participation by students in high school. Does the school garden contribute as a thematic proposal for science teaching? In a school in the State Education network of the State of Goiás, located in the city of Aparecida de Goiânia, in a natural environment, through the STEAM Approach with an interdisciplinary bias through the Teaching Maker Proposal (PME), involving the prototyping of a vegetable garden school, a compost bin and automated irrigation using Arduino. Participating in the research were the researcher with a degree in Biology and the two teachers from related areas (Physics, Robotics), and students from the third grade, class A, from high school, from the morning shift, made up of 30 students, 10 of whom were male. male and 20 female, in an age range of 16-18 years. The dynamics consisted of three weekly moments: garden maintenance; after-school classes via Google Meet and practical classes focusing on prototyping. The methodological procedures were characterized by participant observation, a logbook, and WhatsApp records. In the end, it was possible to analyze that the PME, inserted in the STEAM approach with an interdisciplinary bias, corresponded to greater student performance throughout the entire research. Such results demonstrate and validate the application of these active teaching methodologies, seeking better performance in the process of assimilating scientific concepts. Forming conscious, critical and educated citizens in their rights and duties in the construction of knowledge.